Designing the extruding process of LLDPE/HDPE-Alumina blends using two-level factorial method for conductivity level optimizing HVDC cable insulation material - Mohd Jamil, Mohamad Kamarol; Mohd Noor, Syatirah; Ab Ghani, Sharin; Muhamad, Nor Asiah; Abdul Halim, Khairul Anwar (School of Electrical Engineering and Informatics, 2024)
Several researchers are investigating the polymer nanocomposite usage as electrical insulating materials since it has attracted their attention. The aims are to determine an appropriate nanocomposite blending for the optimization of the dielectric insulation performance. Extruding is one of the main process in blending the composite material. The ideal blends with mixed nanofillers are determined using a conventional technique like the onefactor-at-a-time (OFAT) method. This traditional method required a large number of samples to achieve the blended optimization that could increase the time and cost. In this work, Design of Experiment (DOE) method was used to find the optimization of compounding process using The Two-Level Factorial. The new insulation material contains linear low-density polyethylene (LLDPE) and high-density polyethylene (HDPE) blends with aluminium oxide (Al2O3) nanofillers being tested in this study. The research on employing compounding polymer-based nanocomposite as a high voltage direct current (HVDC) cable insulating material is presented. In this research, the sample is compounded with twin screw extruder that need 3 factors to be set which are: the concentration of the material, rotation per minute of screw speed and the temperature of the machine. The conductivity of the blended samples is measured and analyzed. The crystallinity of the samples also being tested to see the effect of the compounding process. Trough the DOE approach, eight samples are required to be produced to find the optimization in compounding process. The results found that there is enhancement in the conductivity and performance of the samples by optimizing the concentrations of nanofillers to the LLDPE/HDPE-Nanocomposite. This saves a great deal of time and money in contrast to the command approach, which is a one-of-the-time (OFAT) method. Weightage has the most noticeable impact on the sample's conductivity, as shown by the DOE results, which show a percentage contribution of 73.67%. The response surface plot indicates that the optimal weightage concentration and temperature for the LLDPE/HDPE-Alumina that yields the lowest conductivity level are 5wt% and 180OC, respectively. It can be concluded that DOE is a feasible alternative to determine the optimum processing condition using twin screw extruder in sampling the compounding of LLDPE/HDPE-Alumina, which in turn, helps improve the conductivity of these polymer nanocomposite with the low conductivity value.